Estabilização da Equação de Berger-Timoshenko como Limite Singular da Estabilização Uniforme do Sistema de Von-Kármán para Vigas - Souza, Pammella Queiroz de (2012)
We consider a dynamical one-dimensional nonlinear Von Kármán model for beams depending on the parameter " > 0 and we study their asymptotic behavior for t large, when " ! 0. Introducing appropriate damping mechanisms we show that the energy of solutions of the corresponding damped models decay exponential uniform with respect to the parameter ". In order for this to be true the damping mechanism has to have the appropriate scale with respect to ". In the limit as " ! 0 we obtain damped Berger- Timoshenko beam model for which the energy tends exponentially to zero. This is done both in the case of internal and boundary damping .